Aplikasi Berbasis Web untuk Menyusun Laporan Laba Rugi dan Pencatatan Piutang dengan Metode Aging Schedule di Perusahaan Dagang: (Studi Kasus: Toko Agus, Labuhan Maringgai, Lampung Timur) - Septiana, Della; Sukawati, Renny; Kastaman (eProceedings of Applied Science, 2024)
Toko Agus is located in Labuhan Maringgai, East Lampung. This shop has problems in recording sales and customer receivables that are not effective and efficient so that they are often inaccurate in recording reports. So that these problems are resolved, a web based application is needed that can provide accurate information. The application is made using the Laravel framework and the database used is MySQL and this application is built with the waterfall model of the System Development Life Cycle (SDLC) method. The purpose of this system is to facilitate the recording of sales and recording of receivables and the preparation of financial reports. The development of this application is carried out using the Unified Modeling Language (UML). The functionality of the application created includes the process of cash and credit sales transactions, recording the age of accounts receivable, recording sales reports, displaying accounts receivable analysis, and displaying income statements. Keywords: Application, Accounts Receivable, Cash, Trading Company, Aging Schedule Method